DETERMINATION OF THE AMOUNT OF VITAMINS IN FISH FOOD (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The need for vitamins in intensive fish farming in ponds and industrial fish farms has already been determined to a large extent. A lack of vitamins in feed during long-term fish farming under high stocking density in ponds, especially in cages and pools, can lead to vitamin deficiency. This causes metabolic disorders, delayed enzyme synthesis, poorer digestibility and the development of fish diseases. As a result, feed costs for growth increase and growth cessation is observed. To prevent vitamin deficiency, it is necessary to provide fish with the appropriate vitamins. Almost all vitamins must be supplied with food in certain quantities, as they are essential for fish nutrition.